Endoplasmic reticulum-mitochondria crosstalk: new mechanisms in the development of atherosclerosis - Li, Mingxiao; Xiao, Yili; Dai, Ling; Chen, Simin; Pei, Wanjuan; Tan, Chao (Frontiers in Endocrinology, 2025)
Atherosclerosis (AS) is a global public health concern and involves a complex pathogenesis characterized by lipid abnormalities, oxidative stress, and inflammatory responses at the cellular and molecular levels. The crosstalk between the endoplasmic reticulum (ER) and mitochondria, mediated by mitochondria-associated membranes (MAMs), plays a critical role in the pathogenesis of atherosclerosis. As two key cellular organelles, the ER and mitochondria interact physically and functionally through MAMs, which serve as bridges between their close contact and interdependence. MAMs maintain lipid homeostasis, promote calcium ion transport, the oxidative stress response, apoptosis, and autophagy. Recent studies have highlighted the significance of ER-mitochondria crosstalk in the progression of AS, as indicated by mitochondrial and ER structural and functional integrity, redox homeostasis, and calcium homeostasis. This review comprehensively explores the novel mechanisms of ER-mitochondria crosstalk in AS and emphasizes the potential of MAMs as therapeutic targets, aiming to provide new perspectives and strategies for the treatment of cardiovascular diseases.